Synergistic Approach of High-Precision 3D Printing and Low Cell Adhesion for Enhanced Self-Assembled Spheroid Formation - Chunxiang Lu; Aoxiang Jin; Chuang Gao; Hao Qiao; Huazhen Liu; Yi Zhang; Wenbin Sun; Shih-Mo Yang; Yuanyuan Liu (Biosensors)
Spheroids, as three-dimensional (3D) cell aggregates, can be prepared using various methods, including hanging drops, microwells, microfluidics, magnetic manipulation, and bioreactors. However, current spheroid manufacturing techniques face challenges such as complex workflows, the need for specialized personnel, and poor batch reproducibility. In this study, we designed a support-free, 3D-printed microwell chip and developed a compatible low-cell-adhesion process. Through simulation and experimental validation, we rapidly optimized microwell size and the coating process. We successfully formed three types of spheroids—human immortalized epidermal cells (HaCaTs), umbilical cord mesenchymal stem cells (UC-MSCs), and human osteosarcoma cells (MG63s)—on the chip. Fluorescent viability staining confirmed the biocompatibility and reliability of the chip. Finally, drug response experiments were conducted using the chip. Compared to traditional methods, our proposed strategy enables high-throughput production of size-controlled spheroids with excellent shape retention, while enhanced gas exchange during culture improves differentiation marker expression. This platform provides an efficient and cost-effective solution for biosensing applications, such as drug screening, disease modeling, and personalized therapy monitoring. Furthermore, the chip shows significant potential for real-time in vitro monitoring of cellular viability, reaction kinetics, and drug sensitivity, offering valuable advancements in biosensor technology for life sciences and medical applications.